Measurement of Visceral Adipose Tissue using Abdomen CT scan As A Predictor of Type 2 Diabetes Mellitus at H. Adam Malik General Hospital Medan - Nasution, Duma Ratna Sari; Putri Chairani Eyanoer; Pase, M Aron; Lubis, Netty Delvrita (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
ABSTRACT Background: Obesity is a condition where the BMI is â‰¥ 25 kg/m2. Deposition of visceral adipose tissue (VAT) in obese conditions is a predictor of the incidence of type 2 diabetes mellitus. CT scan is an accurate measurement of VAT. A cut-off point value is needed to determine the stratification of VAT at risk for type 2 DM. Method: Cross-sectional study of patients undergoing CT scans of the abdominal area at the Radiology Installation of H. Adam Malik General Hospital, Medan during February 2024. Some of the data was taken from the Master of Clinical Medicine study in 2022. Data was collected in the form of examination BMI, waist circumference, DM risk score, and VAT volume in patients examined by abdominal CT scan at L4 level. The DM risk score was obtained using the ADA diabetes risk score questionnaire. VAT volume measurement using 3D segmentation tools. Results: Of the 116 patients studied, the number of samples was 53,4% male and 46,6% female. High DM risk score proportion of 59,5 %. The most frequent DM risk score was 5. Spearmanâ€™s correlation is used too. The best cut-off point between sensitivity 44.93% and specificity 80,85% is 1.311,9 cm3. The accuracy of CT scan as a predictor of type 2 DM is good (AUC 0.7). The positive predictive value (PPV) is 77,50%, and the negative predictive value (NPV) is 50%. The positive likelihood ratio value (LR +) is 2,34 and the negative likelihood ratio value (LR -) is 0,68. Conclusion: VAT measurement using abdominal CT scan as a predictor of type 2 DM has good accuracy. Keywords: Visceral adipose tissue, cut off, diabetes mellitus, body mass index, waist circumference, abdominal CT scan